GOOD CORPORATE GOVERNANCE, GREEN INOVATION AND SUSTAINABILITY PERFOMANCE - Kautsar Mubarak; Holiawati; Sugiyanto (ZILLZELL MEDIA PRIMA, 2024)
This study aims to examine the influence of Good Corporate Governance and Green Innovation on Sustainability Performance. This type of research is quantitative associative. The data used is secondary data obtained from the company's www.idx.co.id and website. The population in this study is companies that are members of the Sri Kehati Index Listed on the IDX for the period of 2019 – 2023. Meanwhile, the sample of this study was determined by the purposive sampling method so that 20 sample companies were obtained. The analysis method used is Panel Data Model Regression analysis. The results of this study show that Good Corporate Governance and Green Innovation have an effect on Sustainability Performance, Good Corporate Governance has an effect on Sustainability Performance and Green Innovation has an effect on Sustainability Performance.